College students' evolution of ideas in geometrical optics using inquiry-based materials - Rosaroso, Nelson A. (2006)
This study aimed to look into the college students' evolution of ideas in geometrical optics using inquiry-based materials at the University of San Carlos Talamban. A case study of three student participants in an inquiry-based physics course for prospective high school teachers was used. Data were gathered from participant observations, transcripts of small group discussions, students daily learning journals and responses to worksheets and interviews. It was revealed that CPU lesson materials and its learning strategies provided a learning environment where student participants developed scientific ideas on geometrical optics. Student participants' involvement in lab activities and writing a learning journal also influenced conceptual change. The evolution of ideas from the initial to the final were well documented in this study.